Factors Influencing the Choice between Radioactive Iodine and Surgery in the Treatment of Graves' Disease - Nako, Shyuhei; Kawano, Ryota; Minamino, Taishi; Uno, Atsuhiko (International Journal of Practical Otolaryngology, 2025)
There are three established treatment options for Graves' disease: Antithyroid drugs (ATDs), radioactive iodine (RAI) therapy, and surgery. Although ATDs are often selected as the first-line treatment, the optimal treatment approach when ATDs cannot be used or when transitioning from ATDs to other treatment options remains unclear. In this study, we analyzed the factors influencing the choice between RAI and surgery for such patients referred to our department. During the study period, 141 patients (56.4%) were treated with RAI and 109 (43.6%) with surgery; 96% of the patients had previously been treated with ATDs. Among those undergoing surgery, surgery was unavoidable in 38.5%, as RAI was contraindicated for reasons such as pregnancy, breastfeeding, ophthalmopathy, adolescence, comorbid thyroid cancer, or a strong desire by the patient to avoid RAI. The remaining 61.5% opted for surgery, which was recommended for them by clinicians based on several factors, including younger age, severe adverse reactions to ATDs, history of thyroid crisis, and greater thyroid weight. Although these factors independently contributed to the decision to select surgery, they did not entirely rule out the possibility of RAI treatment. The final decision was influenced by both clinical factors and the preferences of the patients and clinicians, indicating the potential for the treatment choice to vary across different medical facilities. This study highlights the importance of a personalized approach in selecting between RAI and surgery for patients with Graves' disease.
Keywords: Graves' disease; antithyroid drug; radioactive iodine; thyroidectomy; treatment selection